Development Of Saltwater Lamp Using Different Type Of Fuel Cell To Increase Its Efficiency - Nur Shafinas, Idris (2023)
The objective of the experiment is to study the performance of saltwater lamps with a different type of fuel cell. The experiment for Al- air fuel cell started by using a complete setup of Al-air fuel cell with four aluminum plates and four air cathodes submerged in 350 ml water with 20gram of salt to form salt electrolyte into the case then it was connected to multimeter for voltage and current reading. The experiment was repeated using Al-Cu fuel cell which used four aluminum and four copper plates. Both fuel cells were tested for 30 minutes. According to the result obtained, Al-air has better brightness compared to Al-Cu fuel cell. Al-Cu fuel cell’s power density reading is lower than Al-air fuel cell. In conclusion, Al-air is recommended for the optimization of the saltwater lamp but al alloy material was proposed for the self-prevention and by-product formation.